Engagement in Medical Research Discourse A Multisemiotic Approach to Dialogic Positioning - Fryer, Daniel Lees (Routledge Studies in Multimodality, 2022)
"This book integrates insights from dialogic theory and systemic functional linguistics (SFL) to extend our understandings of engagement in medical research articles, going beyond notions of the role of verbal dialogue to encompass mathematical and visual semiotics and consider text not just as language but as multisemiosis. The volume begins by outlining the engagement framework and offering a brief overview of historical developments in medical research discourse. This discussion culminates in the introduction of the corpus used for analysis, drawing on original research articles from key medical journals to explore verbal, mathematical, and visual engagement in turn. A subsequent chapter brings these perspectives together to demonstrate intersemiotic engagement across different stages and phases of the medical research article and how such resources work together to construe and maintain the authoritative position commonly associated with medical discourse. The book looks ahead to engagement in other related disciplinary fields and future directions for work on multisemiosis and medical research discourse more generally. This book will be of particular interest to graduate students and researchers in multimodality, critical discourse analysis, applied linguistics, SFL, and science education."